Arsenic-induced immunomodulatory effects disorient the survival-death interface by stabilizing the Hsp90/Beclin1 interaction. (January 2020) - Jamal, Zarqua; Das, Joydeep; Ghosh, Sayan; Gupta, Anasuya; Chattopadhyay, Sreya; Chatterji, Urmi
Abstract: Ground water arsenic contamination is a global menace. Since arsenic may affect the immune system, leading to immunesuppression, we investigated the effects of acute arsenic exposure on the thymus and spleen using Swiss albino mice, exposed to 5 ppm, 15 ppm and 300 ppm of sodium arsenite for 7 d. Effects on cytokine balance and cell survivability were subsequently analyzed. Our data showed that arsenic treatment induced debilitating alterations in the tissue architecture of thymus and spleen. A dose-dependent decrease in the ratio of CD4 + -CD8 + T-cells was observed along with a pro-inflammatory response and redox imbalance. In addition, pioneering evidences established the ability of arsenic to induce an up regulation of Hsp90, eventually resulting in stabilization of its client protein Beclin-1, an important autophagy-initiating factor. This association initiated the autophagic process, confirmed by co-immunoprecipitation assay, acridine orange staining and Western blot, indicating the effort of cells trying to survive at lower doses. However, increased arsenic assault led to apoptotic cell death in the lymphoid organs, possibly by increased ROS generation. There are several instances of autophagy and apoptosis taking place either simultaneously or sequentially due to oxidative stress. Since arsenic is a potent environmental stress factor, exposure to arsenic led to a dose-dependent increase in both autophagy and apoptosis in the thymus and spleen, and cell death could therefore possibly be induced by autophagy. Therefore, exposure to arsenic leads to serious effects on the immune physiology in mice, which may further have dire consequences on the health of exposed animals. Graphical abstract: Image 1 Highlights: Arsenic causes cellular disorganization of thymocytes and splenocytes. ROS has a key role in mediating the cytotoxicity of sodium arsenite in the immune organs. High level of ROS stimulates autophagic/apoptotic pathways responsible for inducing cell death. Hsp90 protein plays a crucial role in Beclin-1 stabilization and upregulation of autophagy upon arsenic exposure.